2016
DOI: 10.1016/j.jjcc.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography of the pulmonary arteries: A systematic review

Abstract: Optical coherence tomography (OCT) is an imaging technique extensively used for visualizing the coronary circulation, where it assists clinical decision-making. Along with the new interventional procedures being introduced for pulmonary vascular disease, there is an increasing need for intravascular imaging of the pulmonary arteries. Additionally, measurements of the wall thickness of the pulmonary arteries of patients with various types of pulmonary hypertension (PH) may provide relevant diagnostic and progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…The technique of optical coherence tomography (OCT) has led to significant advancements in intravascular imaging, which has enabled precise examination of PA morphology. Recent reports have shown that OCT is useful not only for the diagnosis of pulmonary hypertension, but also for evaluation of the response to treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The technique of optical coherence tomography (OCT) has led to significant advancements in intravascular imaging, which has enabled precise examination of PA morphology. Recent reports have shown that OCT is useful not only for the diagnosis of pulmonary hypertension, but also for evaluation of the response to treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As in previous OCT imaging studies we found that PH per se is associated with a significant thickening of pulmonary arteries 13 15 16 . Due to the novelty of OCT imaging in pulmonary arteries there is a lack of standardization as yet 17 . Previous OCT studies reported on more proximal vessels, usually 3–4 mm in diameter, where changes observed are likely to reflect secondary consequences of elevated pressures rather than the site of underlying pathology in the muscular pulmonary arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…This decision to focus primarily on non-OCT based coherence based optical tissue sensing stems from the fact that OCT is a very well-established clinical technique that has previously been extensively reviewed [2938]. We also note that recent advances in Fourier and spectral domain Doppler-OCT have been developed to enable functional sensing of blood flow velocities within intact tissues – also termed optical microangiography – and are well-described elsewhere [3942].…”
Section: Coherence-based Sensing Approachesmentioning
confidence: 99%